Technical Efficiency and Profitability of Smallholder Dairy Cattle Farming Post-FMD: A Stochastic Frontier Analysis in West Java - Faiz Alfian Nazri; Netti Tinaprilla; Anna Fariyanti; Lukman Mohammad Baga (Jurnal Manajemen dan Agribisnis, 2026)
Background: The study is motivated by the persistent low productivity of dairy cattle farming in Bogor Regency, specifically within the Kawasan Usaha Peternakan (KUNAK), which has been further aggravated by the Foot and Mouth Disease (FMD) outbreak and inefficient input management in the area. The sector faces significant challenges, including the dominance of smallholder farms with poor feed management, shrinking land for forage, and heavy reliance on imports, all of which weaken local farmers’ bargaining power.Purpose: This study aimed to analyze the factors influencing milk production, technical efficiency, and farm profitability in KUNAK. It seeks to evaluate how effectively farmers manage inputs, such as cattle and feed, to maximize output and determine the financial feasibility of these operations post-FMD.Design/methodology/approach: Data were collected from 67 purposively sampled farmers in Cibungbulang and Pamijahan (January–April 2025) who owned cows in their second or third lactation. This study utilized a stochastic frontier translog production function estimated via Maximum Likelihood Estimation (MLE) to measure technical efficiency, alongside a revenue-cost (R/C) ratio analysis for profitability.Findings/Result: MLE results indicated that lactating cows (0.656), concentrate (0.193), and tofu dregs (0.159) significantly affected milk yield. Conversely, labor's negative elasticity (-0.083) reflects severe overutilization. The farms operate under increasing returns to scale, with a high mean technical efficiency of 0.868. Efficiency improves with farmer age but declines as the number of family dependents increases. While economically feasible (R/C ratio=1.10), operations face tight profit margins of Rp207,951 per head per month.Conclusion: Although smallholder dairy farming in the KUNAK cluster demonstrates high technical efficiency (0.868), this operational mastery does not translate into proportional economic welfare due to low market pricing and high input costs. Policy interventions must target labor reallocation and cooperative pricing reforms to bridge the gap between technical proficiency and economic sustainability.Originality/value (State of the art): This study contributes a post-FMD analysis of smallholder dairy clusters, revealing a critical disconnect where high technical efficiency does not guarantee economic welfare due to external market and institutional failures. Keywords: dairy cattle, production function, profitability, stochastic frontier, technical efficiency